2017
DOI: 10.1007/s10792-017-0609-0
|View full text |Cite
|
Sign up to set email alerts
|

How accurate is an LCD screen version of the Pelli–Robson test?

Abstract: Computer-generated versions of Pelli-Robson test, displayed on LCD systems, do not provide accurate results compared to classic Pelli-Robson printed version. Clinicians should consider that Pelli-Robson computer-generated versions could be non-interchangeable to the printed version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…They concluded that the newly developed numbers CS charts were inexpensive and could replace the Mars CS chart [1]. Zeri et al [11] checked the accuracy and repeatability of the computerized Pelli-Robson chart displayed on LCD systems against its standard printed version and found that the computer test is not interchangeable with the standard chart. Mohammadi et al [2] examined the degree of agreement between the CS results of the Freiburg visual acuity and contrast test (FrACT) and the Monpack3 device (Metrovision, Perenchies, France) in both amblyopic and normal eyes.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the newly developed numbers CS charts were inexpensive and could replace the Mars CS chart [1]. Zeri et al [11] checked the accuracy and repeatability of the computerized Pelli-Robson chart displayed on LCD systems against its standard printed version and found that the computer test is not interchangeable with the standard chart. Mohammadi et al [2] examined the degree of agreement between the CS results of the Freiburg visual acuity and contrast test (FrACT) and the Monpack3 device (Metrovision, Perenchies, France) in both amblyopic and normal eyes.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it suffers from the limitations of LCDs, mainly represented by the lack of low levels of contrast ratios 18 . The CS grating test measurements provided by the Vision Chart have not yet been investigated (only the Pelli-Robson test performed with this instrument has been analyzed and found to offer repeatable measurements) 19 . Therefore, the aims of this study were to define a normative database of these measurements and to validate them by assessing their repeatability and determining their responsiveness to cataract surgery.…”
Section: Introductionmentioning
confidence: 99%
“…There are also psychophysical methods to determine a gamma luminance function visually, as, for example, described by To et al 6 This report will show that using a gamma-fitted (approximate) luminance function instead of the actual (exact) luminance function may give increasingly larger errors in contrast when displaying stimuli with smaller contrasts. This might also be (part of ) the reason why investigations such as those of Thayaparan et al 7 and Zeri et al 8 did not find a good correlation between a paper and a display version of a contrast sensitivity test for small contrasts.…”
mentioning
confidence: 98%